Personality of the Main Character in The Greatest Showman Movie - Mahesanti, Desak Gede Tarisa; Utami, Gek Wulan Novi; Laksminy, Luh Putu (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study examines the personality of the character P.T. Barnum in the film The Greatest Showman using the Five-Factor Personality theory. This film, as a modern literary work, presents a charismatic, ambitious, and complex main character, making it interesting to analyse in a more psychologically deep way. The purpose of this study is to identify Barnum's dominant personality and understand how this personality affects his social life, especially in marriage and career. The method used is descriptive qualitative by analysing important scenes in the film, including dialogue, expressions, and character interactions. The results of the study indicate that Extraversion and Openness to Experience are the two most prominent personality dimensions in Barnum. These two traits support his success in attracting public attention and building an entertainment business, but also cause tension in his relationships. These findings indicate that personality not only influences the actions of the character but also shapes the direction of his life and interactions with the surrounding environment. This study is expected to enrich the study of literary psychology, especially in understanding the dynamics of characters in films as a form of contemporary literature.